2018
DOI: 10.1159/000493631
|View full text |Cite
|
Sign up to set email alerts
|

EYA4 Promotes Cell Proliferation Through Downregulation of p27Kip1 in Glioma

Abstract: Background/Aims: Accumulating evidence suggests that Eyes Absent Homologue 4 (EYA4) plays an important role in tumorigenesis and progression of various cancers. However, the role of EYA4 in glioma development is still unclear. Methods: The expression of EYA4 was examined in glioma tissues by immunohistochemistry. Cell viability and apoptosis were analyzed by CCK-8, BrdU assay, and flow cytometry. Results: We found that EYA4 was upregulated in glioma, and its expression was positively correlated with advanced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Further investigation by live imaging and the FUCCI system demonstrated that cells silenced for EYA4 undergo slower DNA synthesis, halting cell cycle progression, and undergoing endoreplication as a result of missed mitosis initiation. Our data are in line with previous observations in glioma where EYA4 over-expression promotes cell proliferation by directly suppressing the expression of p27 KIP1 , suggesting p27 KIP1 as a transcriptional target of EYA4 [ 48 ].…”
Section: Discussionsupporting
confidence: 93%
“…Further investigation by live imaging and the FUCCI system demonstrated that cells silenced for EYA4 undergo slower DNA synthesis, halting cell cycle progression, and undergoing endoreplication as a result of missed mitosis initiation. Our data are in line with previous observations in glioma where EYA4 over-expression promotes cell proliferation by directly suppressing the expression of p27 KIP1 , suggesting p27 KIP1 as a transcriptional target of EYA4 [ 48 ].…”
Section: Discussionsupporting
confidence: 93%
“…EYA4 promoter is covered with CpG island, and alternation of DNA methylation was observed in tumor samples compared to normal samples [ 17 , 30 ]. Additionally, abnormality of EYA4 expression has been mentioned to contribute to cancer progression for instance, colon cancer [ 31 ], glioma [ 32 ], lung cancer [ 23 ], and bladder cancer [ 26 ]. Also, downregulation of its expression was defined in different sets of colon cancers, suggesting its role in inhibiting tumor development [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the latter, MITD1 was positively correlated to homologous recombination deficiency ( Dong et al, 2022 ). The gene Eyes absent homolog 4 ( EYA4 ) plays a putative tumor-promoting role in nervous system tumors ( Chong et al, 2023 ) and was found to promote cell proliferation in GBM ( Li et al, 2018b ). Transmembrane BAX inhibitor motif containing 6 ( TMBIM6 ) is elevated in GBM but may be downregulated in other tumor entities; it may be associated with tumor growth and dependent signaling ( Yi et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%